(untitled) (SAARC Journal of Agriculture, 2020)
The study was conducted to reveal various seedling production scenario on floating beds including environmental aspects associating seedling production. Data of various seeding production were collected from total 50 households (HHs) of two villages at Nazirpur Upazila in Pirojpur district of Bangladesh by a pre-tested survey questionnaire. The study showed that 68% farmers did seedling production for business purpose, and 30% as both own and business. During floating cultivation on beds about 50% farmers used their own producing seed and 26% from market. The farmers cultivated 21 different types of vegetables and spices seedlings where highest number of seedling was Bottle gourd (19.11%) followed by Papaya (13.82%) and Chili (12.60%). They used urea as a common fertilizer on floating bed which enriched by TSP (46%) and DAP (40%) during cultivation. It was observed that 32% farmers did seedling cultivation solely as own source of money while 26% got the help from NGOs. After end of the cultivation, 25% beds were sold as compost fertilizer for winter cultivation, 5% were used as own field and 17% farmers utilized the fertilizer as both business and own purpose. The study also revealed that, about 64% of respondent farmers were not suffered by any environmental complications. Adopting modern agrotechnology and minimization of initial cost through subsidy can make this traditional Vasoman Chas has a sustainable agricultural practice. SAARC J. Agri., 18(1): 239-250 (2020)